Assessment of attitudes and practices towards COVID-19 pandemic: a survey on a cohort of educated Syrian population - Lina Albitar; Ghalia Aboualchamat (SpringerOpen, 2023)
Abstract Background Coronavirus disease (COVID-19) caused the death of millions of people and affected the lives of hundreds of millions worldwide. The WHO recommendations aimed mainly to reduce transmission, minimize infection, and get people vaccinated. Nevertheless, opinions and attitudes about the disease varied. In this study, we evaluated personal attitudes and practices of a cohort of an educated Syrian population, after several waves of infection with COVID-19 and the release of different types of vaccines. Methods A cross-sectional internet-based survey was launched in January 2022.The survey queried the participants' personal experience, attitudes, practices towards COVID-19, and vaccination. Results The study included 408 individuals. The respondents were mainly females (72.6%), 20-29 years old (39.2%), and college graduates (59.3%). A large proportion (89.7%) reported having been infected at least once during the pandemic; a significant association was found with age (p = 0.001). Nearly half of the respondents got vaccinated; the majority were > 40 years old. Opinions differed regarding the effectiveness and safety of the vaccines; only a small percentage of the participants (17.4%) thought all vaccines were effective and safe. Remarkably, the level of education did not significantly dominate the participants' attitudes or practices towards the COVID-19 pandemic. Approximately half of the respondents (44.9%) stated their lives were affected by the pandemic and over the third were worried (38%). A significant association was detected with gender in favour of females. Most of the participants have taken at least one precautionary measure to limit the infection. Conclusion The level of education did not significantly dominate the participants' attitudes or practices towards the COVID-19 pandemic. Female respondents were more cautious, concerned and committed to taking precautionary measures regardless of their education level. However, their unwillingness to receive the vaccine raises significant concerns. Efforts should be made to emphasize the importance of immunization, the safety and effectiveness of vaccines, and encourage vaccination among individuals.